Community Library for Education for Sustainable Development in Nigerian Digital Age - Agbeniaru Omigie, Christopher; Osasu Makinde, Theresa; Oboite, Anthony Solomon (Ghana Library Journal, 2023)
This paper is on Community Library for Education for Sustainable Development (ESD) in Nigerian Digital age. The paper is an analytical perspective of literature and recognizance survey conducted on community library as a fundamental hub that connect communities with preserved information and cultural heritage for the Nigerian ESD. In the paper are the relevance of library information resources for the speedy advancement of research and development for a digital Nigeria. The idea of Education for Sustainable Development (ESD) as a school curriculum package with a worldwide standard of teaching and learning is treated to equip the indigenous learners with skills and knowledge to be able to work in a global market place with a universal knowledge base. Correspondingly is the correlation between community library and the ESD through digital access and use of resources for new novelties in the society. Various challenges of the Nigerian Education system and as they affect the ESD were identified and the ways forward suggested.